KEPERCAYAAN ORANG TUA TERHADAP GURU LAKI-LAKI DI TK KARTIKA II-26 KECAMATAN TANJUNG KARANG - Rizka, Rosidah; Syafrudin, Ulwan; Nopiana, Nopiana (DUNIA ANAK: Jurnal Pendidikan Anak Usia Dini, 2023)
Male teachers in kindergarten are role models for students, especially male students. The purpose of this study was to determine how much parents trust male teachers in Kartika II-26 Kindergarten, Tanjung Karang District. The approach used in this research is a quantitative approach with a survey method. Data collection techniques with questionnaires and documentation, questionnaires distributed to parents as many as 35 respondents with the specification of parents whose children are taught by male teachers. The data analysis technique uses descriptive analysis. The results showed that parents still have trust in male teachers who teach at Kartika II-26 Kindergarten with a percentage of trust in the integrity dimension of 84%, the ability dimension of 78.8% and the Benevolence dimension of 84.7% in the average of each dimension of parental trust in male teachers at Kartika II-26 Kindergarten of 82.5%. This proves that male teachers are still trusted by parents.